Fatores intervenientes na relação entre audibilidade de sons de fala e desenvolvimento de linguagem oral - Deperon, Tatiana Medeiros (2018)
Introduction: The child's auditory experiences are influenced by the audibility of speech sounds. These experiences are modified by hearing loss, thereby altering developmental opportunities. Audibility, which can be measured by SII, has been shown to be a necessary condition for language development, since it allows access to the linguistic input. Several factors influence the development of these children and will moderate the relationship between their hearing loss and the results that each child will achieve. Vocabulary development has been shown to be a good indicator of language development. On this perspective, considering that audibility for speech sounds may not be sufficient for the development of oral language, it is necessary to analyze how these factors can interfere in the course and in ways to develop processes that facilitate rehabilitation. Objective: To identify the factors related to the development of oral language when audibility was established for speech sounds in hearing impaired children using who are hearing aid (HA) users. Methods: Sixty-five children aged 6 to 17 years old, HA users and based in the state of São Paulo, were evaluated for their receptive vocabulary performance (PPVT-4) and the relation to the following aspects: socioeconomic status, maternal education level, speech-language therapy, etiology, risk factors for hearing loss, age at diagnosis and intervention, use of the device, hearing and language categories, speech perception and audibility. Results: Within the population analyzed, audibility did not determine vocabulary performance. The variables: socioeconomic level, etiology, number of risk factors for hearing impairment, device usage and speech perception interfered in vocabulary performance. It was also verified that the chance of belonging to the group which scored greater vocabulary performance gets 84% smaller upon the increase of 1 risk factor, but increases in 55% when using the device for one extra hour per day. By relating chronological age and age equivalent in vocabulary performance, it was noted that the difference between the two indexes increases as subjects move away from the normal curve. It was observed that audibility tends to be higher in the group with higher vocabulary performance, and decreases with distance. In the group with good audibility and poor performance, late diagnosis and intervention and inconsistent device use may have been responsible for below-expected vocabulary performance. Conclusions: Factors such as: early diagnosis and intervention, device use, audibility and speech therapy are essential for language development. However, none of them stand-alone is sufficient to make this development happen, and aspects such as early diagnosis and intervention, device use, audibility and speech therapy are also fundamental for the language development to occur